DYNAMICS OF CELLULAR IMMUNITY OF PATIENTS WITH ACUTE RESPIRATORY VIRAL INFECTIONS AGAINST A BACKGROUND OF AEROSOL INTERFERON TREATMENT - Moskaliuk, V.D.; Sorokhan, V.D. (Інфекційні хвороби, 2013)
The effect of aerosol interferon treatment on the dynamics of T-lymphocytes and their subpopulations CD3+, CD4+, CD8+ and the CD4+/CD8+ ratio in patients with influenza A, influenza B, adenovirus infection and acute respiratory viral infections (ARVI) of unknown etiology has been studied, laferon in a dose of 1000000 UN once a day for 3 days has been found to possess the best remedial effect. The most effective treatment turned out to be in patients with ARVI of unknown etiology.